ANALYSIS OF EFFECTIVENESS OF STATIONARY LIFT NET AND FLOATING LIFT NET OPERATION IN PROBOLINGGO WATERS - Rihmi, Mihrobi Khalwatu; Isdianto, Andik; Wardhani, Mentari Puspa (Directorate of Research and Community Service (DRPM), 2024)
Lift net is a fishing tool that belongs to the lifting net group. In terms of construction, there are two types of lift net, namely: stationary lift net and floating lift net. Stationary lift net are a type of static fishing gear. The advantage of this fishing gear is that it gives fishermen certainty about the fishing location. However, if fishermen are not wise in exploiting fish, the catch will decrease, the reason is that stationary lift net will rely heavily on the stock/abundance of local fish in these waters. This is different from floating lift net which are able to change positions. The method is to pull the lift net with the help of the boat. Usually fishermen will move the position of any lift net when the catch is low or the weather is bad. Thus, research was carried out regarding the effectiveness and efficiency of the operation of the lift net by conducting experimental fishing in Probolinggo waters. The results of the independent t test show a significance value of 0.152, which means there is no difference in catches between the stationary lift net and the floating lift net.